International policy coordination for collaboration in S&T - Jakob Edler (The University of Manchester, Manchester Business School, 2010)
This paper discusses an increasingly important, yet challenging development, the international coordination of nationally rooted policies or funding schemes to support international collaboration in science and technology (S&T). It conceptualizes ways in which government ministries or agencies can realise synergies when it comes to supporting international activities of their researchers. Although the principles developed for international coordination can be generalized, it is set in the context of the European Research Area (ERA). Existing conceptual and empirical analysis has shown that coordination of policy to foster international S&T collaboration is by and large rather poor even domestically. The paper argues that international coordination of national policies for international S&T collaboration meets an additional set of challenges that need to be tackled systematically. The conceptual considerations presented in this chapter can lay the basis for an analysis of current coordination activities. They can, however, also be utilised to design systematic coordination schemes for policies geared towards international collaboration as they provide the major elements of strategic approach for such an international coordination approach.
Keywords: 330; Forschungs- und Technologiepolitik; Internationale wissenschaftliche Zusammenarbeit; Governance-Ansatz; International